PCR para o diagnóstico da campilobacteriose genital bovina - Groff, Ana Cláudia Mello (2005)
Bovine genital campylobacteriosis is a disease of difficult diagnostic because of the microaerophilic nature of its etiologic agent, Campylobacter fetus, thereby causing the prevalence related to this disease to be underestimated. The purpose of this study was to evaluate the utilization of PCR for the diagnosis of genital campylobacteriosis, using samples obtained from bull prepuce aspirate, cow cervical mucus, and abomasum contents obtained from aborted fetuses, collected in transport and enrichment medium. Five different DNA extraction protocols were tested: thermal extraction, lyses with proteinase K, lyses with guanidine isothiocyanate, lyses with DNAzol? , and lyses with CTAB. The specificity, sensitivity and technical application of PCR assay were also evaluated with clinical samples. The PCR performance was compared to the culture technique for bacterial isolation. The CTAB was the most efficient extraction protocol; the pair of primers used was shown to be specific; and the limit of detection was of 63 CFU of Campylobacter fetus. PCR demonstrated that 24% (68/277) of the clinical samples were positive for Campylobacter fetus, while only 2.8% (8/277) of samples were positive by culture techinque. These results indicate that the PCR technique is specific and sensitivy, and is superior to the culture for the diagnosis of bovine genital campylobacteriosis.